2022
DOI: 10.1136/emermed-2021-211934
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of triage tools for adults with suspected COVID-19 in a prehospital setting: an observational cohort study

Abstract: BackgroundTools proposed to triage patient acuity in COVID-19 infection have only been validated in hospital populations. We estimated the accuracy of five risk-stratification tools recommended to predict severe illness and compared accuracy to existing clinical decision making in a prehospital setting.MethodsAn observational cohort study using linked ambulance service data for patients attended by Emergency Medical Service (EMS) crews in the Yorkshire and Humber region of England between 26 March 2020 and 25 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“… Structural/ Systemic 53 Marincowitz et. al 65 Prognostic accuracy of triage tools for adults with suspected COVID-19 in a prehospital setting: an observational cohort study Cohort Patient care reports GB ● 65% of patients were transported to hospital and EMS decision to transfer patients achieved a sensitivity of 0.84. ● NEWS2, PMEWS, PRIEST tool and WHO algorithm identified pts at risk of adverse outcomes with a high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Structural/ Systemic 53 Marincowitz et. al 65 Prognostic accuracy of triage tools for adults with suspected COVID-19 in a prehospital setting: an observational cohort study Cohort Patient care reports GB ● 65% of patients were transported to hospital and EMS decision to transfer patients achieved a sensitivity of 0.84. ● NEWS2, PMEWS, PRIEST tool and WHO algorithm identified pts at risk of adverse outcomes with a high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…The WHO algorithm, PRIEST, NEWS2, and PMEWS tools all had high sensitivity for detecting COVID-19 infection. 65 In Uppsala, Sweden, Mälberg et al report correlational findings of physiological respiratory parameters with patients suspected of having COVID-19. They found that the odds of COVID-19 diagnosis increased with respiratory rate, lower tidal volume, and negative inspiratory pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al report correlational findings of physiological respiratory parameters with patients suspected of having COVID-19. They found that the odds of COVID-19 diagnosis increased with respiratory rate, lower tidal volume, and negative inspiratory pressure (65) . In Paris, France, Jouffroy et.…”
Section: Discussionmentioning
confidence: 99%
“…al studied the accuracy of prognostic triage tools used prehospitally in the Yorkshire and Humber region. The WHO algorithm, PRIEST, NEWS2, and PMEWS tools all had high sensitivity for detecting COVID-19 infection (65) . In Uppsala, Sweden, Mälberg et.…”
Section: Discussionmentioning
confidence: 99%